The Influence of Teachers Against Inquiry Skills Critical Thinking Skills and Learning Outcomes in Biology Education Class VIII SMP Negeri 18 Palu - M. Thahir, Faizah; Tanra Tellu , Andi; Jamhari , Mohammad (Jurnal Riset Pendidikan MIPA, 2017)
The research aims to determine the effect of teacher’s skill in the chemistry instructional toward motivation and learning outcomes of the tenth-grade students of SMA Negeri 1 Palolo. The population was the whole students of the tenth grade registered in academic year 2013/2014 numbered 201 persons and separated in five classes with the sample class XA and class XD totaling 98 persons. The sample was taken purposively. The data were collected through questionnaires of teacher’s skills in chemistry instructional, motivation, and learning achievement tests. The result indicated that each average of teacher’s skill, motivation, and achievement test was 69, 74, and 91. The statistic testing result shows teachers’ skill significantly influenced toward motivation and learning achievement with a coefficient correlation score each was 0.462 and 0.425. The variable contribution of teacher’s skill toward motivation was 21.3%  while the skill contribution toward learning achievement was 18.1%.  Based on the coefficient correlation score, it can be concluded that teachers’ skills in chemistry instructional influenced motivation and learning outcomes categorized enough.